Mettl14 Attenuates Cardiac Ischemia/Reperfusion Injury by Regulating Wnt1/β-Catenin Signaling Pathway - Pang, Ping; Qu, Zhezhe; Yu, Shuting; Pang, Xiaochen; Li, Xin; Gao, Yuelin; Liu, Kuiwu; Liu, Qian; Wang, Xiuzhu; Bian, Yu; Liu, Yingqi; Jia, Yingqiong; et al. (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) RNA participates in many pathological processes of cardiac diseases. This study was designed to investigate Mettl14 on cardiac ischemia-reperfusion (I/R) injury and uncover the underlying mechanism. The levels of m6A and Mettl14 protein were increased in I/R hearts and neonatal mouse cardiomyocytes (NMCMs) upon oxidative stress. Mettl14 knockout (Mettl14+/-) mice showed pronounced increases in cardiac infarct size and LDH release, and aggravation in cardiac dysfunction post-I/R. Conversely, adenovirus-mediated overexpression of Mettl14 markedly reduced infarct size, apoptosis, and led to cardiac function improvement during I/R injury. Silencing of Mettl14 alone significantly caused a decrease in cell viability and an increase in LDH release, and furtherly exacerbated these effects in the presence of H2O2, while overexpression of Mettl14 ameliorated cardiomyocyte injury in vitro. Mettl14 resulted in enhanced levels of Wnt1 m6A modification and Wnt1 protein, but not its transcript level. Furthermore, Mettl14-overexpression blocked I/R-induced downregulation of Wnt1 and β-catenin proteins, whereas Mettl14+/- hearts exhibited the opposite results. Knockdown of Wnt1 abrogated Mettl14-mediated upregulation of β-catenin and protection against injury upon H2O2. Our study demonstrates that Mettl14 contributes to attenuates cardiac I/R injury by activating Wnt/β-catenin in a m6A-dependent manner, providing a novel therapeutic target for ischemic heart disease.